2020
DOI: 10.9758/cpn.2020.18.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Ramelteon for Delayed Sleep-wake Phase Disorder: A Case Report

Abstract: Recently developed melatonin receptor agonists are expected to be effective for delayed sleep-wake phase disorder (DSWPD). To date, however, no study has described the effect of melatonin receptor agonists on DSWPD. We report the case of a 15-year-old girl with DSWPD who was successfully treated with ramelteon 4 mg at 7 PM. DSWPD symptoms were resolved; her sleep-wake and biological rhythms were normalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A 0.5 mg of melatonin 10 to 12 hours before the midpoint of sleep achieves the greatest amount of phase advance 50 . Also, it has been reported that a prescription of 1, 2, or 4 mg of ramelteon or ramelteon and 15 mg of suvorexant improve symptoms of DSPD 51 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 0.5 mg of melatonin 10 to 12 hours before the midpoint of sleep achieves the greatest amount of phase advance 50 . Also, it has been reported that a prescription of 1, 2, or 4 mg of ramelteon or ramelteon and 15 mg of suvorexant improve symptoms of DSPD 51 …”
Section: Resultsmentioning
confidence: 99%
“…50 Also, it has been reported that a prescription of 1, 2, or 4 mg of ramelteon or ramelteon and 15 mg of suvorexant improve symptoms of DSPD. 51…”
Section: Melatoninmentioning
confidence: 99%
“…Administration of 1-4 mg of ramelteon at 30 min before bedtime produces a phase advance. However, no difference in the effect was found between a dose of 8 mg and a placebo (180), suggesting that a small drug dose would be preferable for the treatment of DSWPD (181,182). However, clinical evidence regarding the optimal timing of ramelteon administration for the treatment of DSWPD remains scarce.…”
Section: Chronobiological Approachesmentioning
confidence: 99%
“…MRAs have also been clinically shown to decrease SOL [ 86 89 ] and shift the circadian phase [ 90 92 ]. However this is largely in healthy populations and therapeutic use in DSWPD has yet to be demonstrated save for two recent successful case reports using ramelteon [ 93 , 94 ]. Of these, Shimura et al in particular [ 94 ] suggest that ramelteon should be administered at very low doses for DSWPD.…”
Section: Preamblementioning
confidence: 99%